Environmental Auditing Practices in Iraqi Oil Companies for Sustainable Development: Praktik Audit Lingkungan di Perusahaan Minyak Irak untuk Pembangunan Berkelanjutan - Hashmi , Saddam Catea (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Environmental auditing is essential for assessing corporate environmental performance and ensuring compliance with sustainability regulations.Specific Background: The Iraqi oil sector significantly impacts the environment, yet environmental auditing remains underdeveloped and underexplored. Knowledge Gap: Limited research exists on the role of environmental auditing in achieving sustainability in Iraq’s oil industry, particularly regarding regulatory influence. Aims: This study examines environmental audit requirements and their impact on sustainable development in Iraqi oil companies. Results: Data from 299 auditors and accountants indicate a strong correlation between environmental auditing and sustainable development, despite regulatory challenges. Novelty: The study establishes a direct link between environmental auditing and sustainability, offering a structured framework for corporate sustainability strategies. Implications: Findings highlight the need for stronger regulations, policy reforms, and systematic audits to align the oil sector with global sustainability goals. Highlights: Audit-Sustainability Link – Environmental auditing significantly impacts sustainable development in the oil sector. Regulatory Challenges – Weak enforcement and limited studies hinder effective environmental auditing in Iraq. Policy Implications – Strengthening regulations and systematic audits are crucial for sustainability integration. Keywords: Environmental Auditing, Sustainable Development, Oil Industry, Regulatory Compliance